Symptomy chorobowe i grzyby na zamierających jesionach (Fraxinus excelsior L.) w drzewostanach Nadleśnictwa Staszów - Kowalski, Tadeusz; Czekaj, Artur (Leśne Prace Badawcze, 2010)
An analysis of the health status of 32 stands in the Staszów Forest District showed severe intensity of disease in ash trees ( Fraxinus excelsior ). Among 875 trees of the first age class, 17.0 % were dead and there were disease symptoms on the above-ground parts of 38.7 %. The most-common symptoms on trunks of diseased trees included local necroses with intact bark (type A, on 31.5% of trees) and local bark necroses with xylem exposed by splitting bark (type B, on 8.6% of trees). The most common symptoms in crowns included the death of whole branches (26.7%) or their apices (21.3 %), and tree-top die-back (13.7%). In stands more than 20-years old, 1.7% of trees were dead. Common symptoms on the trunks of living trees included local bark necroses of type A (58.5%) and type B (12.0%) and extended, elongated necroses (41.8%). Dead tops occurred on 12.0% of trees. Dying branches were present in the crowns of all trees, but only in 12.2% of trees were more than 50.0% of branches dead. Crowns of 98.3% of trees showed symptoms of defoliation. Most trees lost less than 25.0% of leaves. Epicormic shoots growing from trunks and along the bases of living branches occurred on 59.5% of trees. Disease symptoms occurred more often in artificially-regenerated stands than naturally-regenerated ones. The comparison of disease intensity on ash trees in different forest habitat types could not be conducted, because 26 out of 32 stands represented wet broadleaved forest. Alternaria alternata, Botryosphaeria stevensii, Chalara fraxinea , Cytospora pruinosa , Diaporthe sp., Didymosphaeria acerina , Fusarium lateritium , Massaria sp., Phomopsis scobina , Phomopsis sp., and Pezicula cinnamomea were the most common fungi on diseased ash trees. Chalara fraxinea seemed to be the main cause of disease.